Cell and tissue manipulation with ultrashort infrared laser pulses in light-sheet microscopy - de Medeiros, Gustavo (Sci Rep, 2020)
Three-dimensional live imaging has become an indispensable technique in the fields of cell, developmental and neural biology. Precise spatio-temporal manipulation of biological entities is often required for a deeper functional understanding of the underlying biological process. Here we present a home-built integrated framework and optical design that combines three-dimensional light-sheet imaging over time with precise spatio-temporal optical manipulations induced by short infrared laser pulses. We demonstrate their potential for sub-cellular ablation of neurons and nuclei, tissue cauterization and optogenetics by using the Drosophila melanogaster and zebrafish model systems.